Behavioral And Eeg Reactions In Native Turkic-Speaking Inhabitants Of Siberia And Siberian Russians During Recognition Of Syntactic Errors In Sentences In Native And Foreign Languages - Astakhova, Tatiana N.; Saprygin, Alexander E.; Golovko, Tatiana A.; Savostyanov, Alexander N.; Vlasov, Mikhail S.; Borisova, Natalia V.; Alexandera G. Karpova; Urana N. Kavai-Ool; Mokur-Ool, Elena; Kolchano, Nikolay A.; Aftanas, Lyubomir I. (Zenodo, 2015)
The aim of the study is to compare behavioral and EEG reactions in Turkic-speaking inhabitants of Siberia (Tuvinians and Yakuts) and Russians during the recognition of syntax errors in native and foreign languages. Sixty-three healthy aboriginals of the Tyva Republic, 29 inhabitants of the Sakha (Yakutia) Republic, and 55 Russians from Novosibirsk participated in the study. EEG were recorded during execution of error-recognition task in Russian and English language (in all participants) and in native languages (Tuvinian or Yakut Turkic-speaking inhabitants). Reaction time (RT) and quality of task execution were chosen as behavioral measures. Amplitude and cortical distribution of P300 and P600 peaks of ERP were used as a measure of speech-related brain activity. In Tuvinians, there were no differences in the P300 and P600 amplitudes as well as in cortical topology for Russian and Tuvinian languages, but there was a difference for English. In Yakuts, the P300 and P600 amplitudes and topology of ERP for Russian language were the same as Russians had for native language. In Yakuts, brain reactions during Yakut and English language comprehension had no difference, while the Russian language comprehension was differed from both Yakut and English. We found out that the Tuvinians recognized both Russian and Tuvinian as native languages, and English as a foreign language. The Yakuts recognized both English and Yakut as foreign languages, but Russian as a native language. According to the inquirer, both Tuvinians and Yakuts use the national language as a spoken language, whereas they do not use it for writing. It can well be a reason that Yakuts perceive the Yakut writing language as a foreign language while writing Russian as their native. : {"references": ["S. Bentin, Electrophysiological studies of visual word perception,\nlexical organization, and semantic processing: a tutorial review. Lang.\nSpeech, 1989, vol. 32 (Pt 3), pp. 205-20.", "S. Bentin, Y. Mouchetant-Rostaing, M. H. Giard, J. F. Echallier, J.\nPernier, ERP manifestations of processing printed words at different\npsycholinguistic levels: time course and scalp distribution. J. Cogn.\nNeuroci., 1999, vol. 11, \u2116 3, pp.235-60.", "E. Pihko, V. V. Nikulin, R. J. Ilmoniemi, Visual attention to words in\ndifferent languages in bilinguals: a magnetoencephalographic study.\nNeuroimage, 2002, vol. 17, \u2116 4, pp. 1830-6.", "A.C. Tsai, A. N., Savostyanov, A. Wu, J. P. Evans, V. S. C. Chien, H.\nH. Yang, D. Y. Yang, M. Liou, Recognizing syntactic errors in Chinese\nand English sentences: Brain electrical activity in Asperger's syndrom.,\nResearch in Autism Spectrum Disorders, 2013, vol. 7, pp. 889-905.", "J. Pellikka, P. Heleniu, J. P. M\u00e4kel\u00e4, M. Lehtonen, Context affects L1\nbut not L2 during bilingual word recognition: an MEG study. Brain\nLang., 2015, vol. 42, pp. 8-17.", "X. Meng, J. Jian, H. Shu, X. Tian, X. Zhou, ERP correlates of the\ndevelopment of orthographical and phonological processing during\nChinese sentence reading. Brain Res., 2008, vol. 1219, pp. 91-102.", "Y. N. Yum, S. P. Law, I. F. Su, K. Y. Lau, K. N. Mo, An ERP study of\neffects of regularity and consistency in delayed naming and lexicality\njudgment in a logographic writing system. Front Psychol., 2014, vol.\n5:315.", "H. W. Boweden, K. Steinhauer, C. Sanz, M. T. Ullman, Native-like\nbrain processing of syntax can be attained by university foreign\nlanguage learners. Neuropsychologia, 2013, vol. 51, \u2116 13, pp. 2492-\n511.", "A. Delorme, S. Makeig EEGLAB: an open source toolbox for analysis of\nsingle-trial EEG dynamics including independent component analysis, J.\nNeurosci. Methods, 2004, vol. 134, \u2116 1, pp. 9\u201321.\n[10] S. Makeig, A. J. Bell, T. P. Jung, T. J. Sejnowski Independent\ncomponent analysis of electroencephalografic data Adv. Neural Inf.\nProcess. Syst., 1996, vol. 8, pp. 145\u2013151."]}